IAAF Kids' Athletics - A team event for children - Gozzoli, C.; Simohamed, J.; Malek El Hebil, A. (2006)
A practical guide for kids' athletics animators. The idea, the aims and concepts of Kids' Athletics, a special program of the IAAF, are presented. "IAAF KIDS` ATHLETICS" is intended to bring excitement into playing Athletics. New events and innovative organisation will enable children to discover basic activities: sprinting, endurance running, jumping, throwing/putting in just about any place (stadium, playground, gymnasium, any available sport area, etc.). The athletics games will provide children with the opportunity to make the most of the beneficial practice of Athletics, in terms of health, education, and selffulfillment.